1980
DOI: 10.1111/j.1540-4560.1980.tb02019.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging Labels: The Decline of Control and the Fall of Self‐Esteem

Abstract: This paper describes several studies that investigated how negative labeling and stigmatization of the elderly might contribute to behavior that would then confirm prevalent stereotypes of old age and lead to lowered self-esteem and diminished feelings of control. First, the nature and extent of labeling processes regarding the elderly were described, followed by a description of studies considering how these stereotypes might affect actual interactions involving older persons. It was found that younger people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
144
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(147 citation statements)
references
References 24 publications
1
144
0
2
Order By: Relevance
“…Applying this theory to ageism, Rodin and Langer (1980) have reported data that though elderly people are generally more positive than non-elderly people towards an elderly target, they can be less positive than non-elderly people if the older target shows signs of forgetfulness. Further, several studies have found that greater self-reported death anxiety predicted more negative attitudes towards elderly people (Depaola, Griffin, & Young, 2003;Hunter, Linn, & Pratt, 1979;Schwiebert, 1978).…”
Section: Ageism and Death: Effects Of Mortality Salience And Perceivementioning
confidence: 99%
“…Applying this theory to ageism, Rodin and Langer (1980) have reported data that though elderly people are generally more positive than non-elderly people towards an elderly target, they can be less positive than non-elderly people if the older target shows signs of forgetfulness. Further, several studies have found that greater self-reported death anxiety predicted more negative attitudes towards elderly people (Depaola, Griffin, & Young, 2003;Hunter, Linn, & Pratt, 1979;Schwiebert, 1978).…”
Section: Ageism and Death: Effects Of Mortality Salience And Perceivementioning
confidence: 99%
“…Given the presumed increase in customers' levels of dominance in the presence of a smiling (versus non-smiling) employee, and research demonstrating that feelings associated with dominance (such as sense of control) have a positive impact on well-being outcomes (De Lange et al, 2003;Langer and Rodin, 1976;Rodin and Langer, 1977;1980;Seligman, 1975), the author predicts that customers' levels of dominance should mediate the effect of employee-displayed smiling on customer satisfaction. However, given that feelings of dominance are less characteristic of a smile than feelings associated with pleasure, dominance should have a weaker influence on customers' subsequent satisfaction judgments compared to pleasure.…”
Section: Accordingly the Author Hypothesizesmentioning
confidence: 99%
“…As such, despite Barger and Grandey's (2006) claim that their study is "the first known study to examine whether mimicry occurs in a service context and whether it explains why service with a smile predicts customer mood" (p. 1231), the validity of their positive affect index can questioned because it taps two distinct affective dimensions in the S-O-R model. Therefore, given that most studies have suggested that pleasure should mediate the effect of employee-displayed smiling on customer satisfaction, and that such a relationship would be justified by emotional contagion and feelings-asinformation theory, the author hypothesizes: H3a: Pleasure mediates the effect of employee-displayed smiling on customer satisfaction.Just as the effect of employee-displayed smiling seems to be less evident for arousal than for pleasure, the mediating influence of arousal on customer satisfaction is likely to be Given the presumed increase in customers' levels of dominance in the presence of a smiling (versus non-smiling) employee, and research demonstrating that feelings associated with dominance (such as sense of control) have a positive impact on well-being outcomes (De Lange et al, 2003; Langer and Rodin, 1976;Rodin and Langer, 1977;1980;Seligman, 1975), the author predicts that customers' levels of dominance should mediate the effect of employee-displayed smiling on customer satisfaction. However, given that feelings of dominance are less characteristic of a smile than feelings associated with pleasure, dominance should have a weaker influence on customers' subsequent satisfaction judgments compared to pleasure.…”
mentioning
confidence: 99%
“…Although the predominant finding in the cognitive gerontology literature is that memory performance tends to decline as people age (Kausler, 1994;Zacks, Hasher, & Li, 1999), some researchers have suggested that the decline may not be inevitable and can be influenced by older adults' stereotypically negative expectations about the aging process itself, as well as through reduced selfefficacy levels (e.g., Lachman, Weaver, Bandura, Elliott, & Lewkowicz, 1992;Langer, Rodin, Beck, Weinman, & Spitzer, 1979;Rodin & Langer, 1980). Although the research on whether self-efficacy beliefs affect memory and cognition across the lifespan has sometimes produced mixed results, there is nonetheless empirical evidence to suggest that positive expectations may be related to enhanced cognitive performance and negative expectations to poorer cognitive performance (Albert, Jones, Savage, Berkman, Seeman, Blazer, & Rowe, 1995;Hertzog, Dixon, & Hultsch, 1990;Ryan, Kwong-See, Meneer, & Trovato, 1992).…”
mentioning
confidence: 99%